Hubungan Paritas, Usia, Dukungan Suami dan Pengetahuan Tentang Pendapat Islam dengan Pemilihan Kontrasepsi Pasangan Usia Subur - Yunitasari, Eva; Oktarosada, Dwi; Agustriyani, Feri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Contraception is the intentional prevention of pregnancy during sexual intercourse. The Family Planning Program is an effort to measure the number and distance of children desired, to achieve this, several ways are made to prevent or delay pregnancy, namely by using the Long-Term Contraceptive Method and non-Long-Term Contraceptive Method. Accomplishment in the selection of contraception is related to various factors, namely, parity, age, husband's support, and knowledge of Islamic views. The research objective was to determine the correlation between parity, age, husband's support, and knowledge of Islamic views with the selection of contraceptives for couples of women reproductive age. This type of research is quantitative descriptive-analytic research with a cross-sectional approach. This research was carried out in Pekon Wonodadi at the working area of the Public Health Center in Gadingrejo of Pringsewu as many as 387 couples of women reproductive age. The sampling technique was consecutive sampling with the statistical test used Chi-Square. The results of the analysis show that there is a correlation between parity with the selection of contraception for couples of women reproductive age (p-value 0.001), there is a correlation between age and the selection of contraception for couples of women reproductive age (p-value 0.004), there is a correlation between husband's support and the selection of contraception for couples of women reproductive age (p-value 0.008). There is a correlation between knowledge of Islamic views and the selection of contraception for couples of women reproductive age (p-value 0.001). It is expected that the health care workers of the public health center can prioritize health promotion to increase the knowledge of couples of women reproductive age in the use of long-term contraceptive methods.Kontrasepsi merupakan pencegahan kehamilan secara sengaja selama hubungan seksual. Program Keluarga Berencana (KB) adalah usaha untuk mengukur jumlah dan jarak anak yang diinginkan, untuk mencapai hal tersebut dibuatlah beberapa cara untuk mencegah ataupun menunda kehamilan yaitu dengan menggunakan Metode Kontrasepsi Jangka Panjang (MKJP) dan non Metode Kontrasepsi Jangka Panjang (non MKJP). Keberhasilan dalam pemilihan kontrasepsi berkaitan dengan berbagai faktor yaitu, paritas, usia, dukungan suami dan pengetahuan tentang pendapat islam. Tujuan penelitian ini untuk mengetahui hubungan paritas, usia, dukungan suami dan pengetahuan tentang pendapat islam dengan pemilihan kontrasepsi pasangan usia subur Di Wilayah Kerja Puskesmas Gadingrejo Kabupaten Pringsewu. Jenis penelitian ini adalah penelitian kuantitatif deskriptif analitik dengan pendekatan cross sectional. Penelitian ini dilaksanakan di Pekon Wonodadi wilayah kerja Puskesmas Gadingrejo Kabupaten Pringsewu sebanyak 387 pasangan usia subur.Teknik pengambilan sampel consecutive sampling dengan uji statistic yang digunakan yaitu Chi Square. Hasil analisa diketahui bahwa ada hubungan paritas dengan pemilihan kontrasepsi pasangan usia subur (p value 0,001), ada hubungan usia dengan pemilihan kontrasepsi pasangan usia subur (p value 0,004), ada hubungan dukungan suami dengan pemilihan kontrasepsi pasangan usia subur (p value 0,008), ada hubungan pengetahuan tentang pendapat islam dengan pemilihan kontrasepsi pasangan usia subur (p value 0,001). Diharapkan bagi tenaga kesehatan puskesmas agar dapat mengedepankan promosi kesehatan guna meningkatkan pengetahuan pasangan usia subur dalam penggunaan metode kontrasepsi jangka panjang.